A novel scoring system predicting survival benefits of palliative primary tumor resection for patients with unresectable metastatic colorectal cancer: A retrospective cohort study protocol. Issue 37 (September 2019) - Cao, Gaoyang; Zhou, Wei; Chen, Engeng; Wang, Fei; Chen, Li; Chen, Min; Zhao, Wei; Xu, Jianbin; Zhang, Wei; Zhang, Guolin; Huang, Xuefeng; Song, Zhangfa
Abstract : Abstract: The role of palliative primary tumor resection (PPTR) in improving survival in patients with synchronous unresectable metastatic colorectal cancer (mCRC) is controversial. In this study, we aimed to evaluate whether our novel scoring system could predict survival benefits of PPTR in mCRC patients. In this retrospective cohort study consecutive patients with synchronous mCRC and unresectable metastases admitted to Sir Run Run Shaw Hospital between January 2005 and December 2013 were identified. A scoring system was established by the serum levels of carcinoembryonic antigen (CEA), cancer antigen 19-9 (CA19-9), neutrophil/lymphocyte ratio (NLR), and lactate dehydrogenase (LDH). Patients with scores of 0, 1–2, or 3–4 were considered as being in the low, intermediate, and high score group, respectively. Primary outcome was overall survival (OS). A total of 138 eligible patients were included in the analysis, of whom 103 patients had undergone PPTR and 35 had not. The median OS of the PPTR group was better than that of the Non-PPTR group, with 26.2 and 18.9 months, respectively ( P < .01). However, the subgroup of PPTR with a high score (3–4) showed no OS benefit (13.3 months) compared with that of the Non-PPTR group (18.9 months, P = .11). The subgroup of PPTR with a low score (52.1 months) or intermediate score (26.2 months) had better OS than that of the Non-PPTR group ( P < .001, P = .017, respectively). A novel scoring system composed of CEA, CA19-9, NLR, and LDH values is a feasible method to evaluate whether mCRC patients would benefit from PPTR. It might guide clinical decision making in selecting patients with unresectable mCRC for primary tumor resection.